Analisis Kelayakan Proyek Pembangunan Pltm Walesi Cascade Secara Nilai Ekonomi Ketenagalistrikan Dan Potensi Kredit Karbon - Hardianto, Fahmi; Sidqi, Ahsin (JURNAL MANAJEMEN PENDIDIKAN, 2026)
FEASIBILITY ANALYSIS OF THE WALESI CASCADE MINI-HYDROPOWER DEVELOPMENT PROJECT IN TERMS OF POWER SECTOR ECONOMIC VALUE AND CARBON CREDIT POTENTIALThe development of the Walesi Cascade Mini Hydropower Plant (PLTM) in Jayawijaya Regency, Papua Province, represents a strategic initiative in supporting Indonesia’s energy transition agenda toward achieving the Net Zero Emission (NZE) 2060 target. As part of the renewable energy mix, mini hydropower has significant potential to reduce dependence on fossil fuels, enhance regional energy resilience, and lower carbon emissions in the electricity sector. This study aims to evaluate the economic feasibility and carbon trading potential of the Walesi Cascade PLTM, while assessing its contribution to clean energy provision and climate change mitigation. The economic analysis utilizes several key indicators. The Levelized Cost of Energy (LCOE) is used to assess total electricity generation costs and demonstrates competitive cost efficiency. The financial analysis shows a positive Net Present Value (NPV), indicating that the project’s benefits outweigh its investment costs. The high Internal Rate of Return (IRR) reflects an attractive investment return. Additionally, the Break-Even Point (BEP) is estimated to be achieved in approximately 8.9 years, and the Benefit-Cost Ratio (BCR) greater than 1 signifies that the economic benefits substantially exceed total expenditures. A favorable Rate of Return (RoR) further strengthens the long-term financial sustainability of the project. From an environmental perspective, this study identifies opportunities for carbon trading through the Voluntary Carbon Market (VCM). The potential generation of carbon credits from emission reductions in the Walesi Cascade PLTM plays an important role in accelerating Indonesia’s transition toward sustainable clean energy.